Financial Leverage and Financial Performance of Nigerian Manufacturing Firms - Norhani Aripin; Ogirima Abdulmumuni (International Journal of Supply Chain Management, 2020)
This paper examined the association between financial leverage and financial performance of Nigerian manufacturing firms. Performance is the ability of management to control firms’ resources to gain competitive advantage. Among the internal organisational factors that affect firms’ profitability is financial leverage which is the firms’ capital structure framework. From agency theory perspective, it is hypothesised that profitability increases with debt financing to a certain optimal level of debts. A five-year data covering a period between 2011 to 2015, sourced from the financial statements of 66 Nigerian manufacturing firms were collected. This study found that financial leverage is positively and significantly associated with the financial performance of Nigerian manufacturing firms, measured as return on equity (ROE). Further, the firms with moderate level of debt ratio are found positively associated with ROE. In contrast, all equity-financed firms and those firms with excessive debts financing are negatively associated with ROE. A positive association is also found between firm size and revenue growth rate with ROE. Nigerian manufacturing firms are recommended to apply agency theory of optimal debts financing to address their financial constraint and poor performance issues.